A go itewa ke monne wa gago ke Botshelo? : a preliminary investigation into battered women in Botswana.Volume1 - Mogwe, Alice (Institute of Criminology, 2023)
This dissertation focusses upon battered women in Gaborone and its environs. It aims to perspective. examine physical battering from a socio-legal In an attempt to link the social and the legal, the women' s theoretical with the 'symbolic' them. and actual responses are analysed together and practical legal remedies available to by using new revolutionary feminism as a methodological and analytical tool, the researcher was able both to: relate to the women as a woman, and - ' create with the women a means of communication which was less hierarchic than it would otherwise have been. The legal and sociological responses are examined against the backdrop of a brief socio-political history of the country. The central themes focussed upon here are the law, role of chiefs, and the role and status of women in both the pre- and post-independence phases. This Chapter also serves to locate the major themes of the dissertation, marriage, family and the law, within a broader socio-political context. A brief excursus focusses on selected Zimbabwean legislation which directly relates to women. Even though the legislation is not specifically for combating battering, its potential use for such purpose becomes clear. Zimbabwe provides an example of a contemporary African country actively involved with putting to paper its government's ·commitment to the liberation of women and the establishment of equality of men and women in all spheres of Zimbabwean society. '1 The recommendations are divided into preferred and interim measures. The preferred measures operable within the researcher's preferred society are aimed at: the elimination of traditional structures which result in oppression and exploitation; the elimination of ideological relations which create and reinforce oppressive social relations at both personal and I global political economic levels; and being a society in which the laws both reflect and effect the principles of equality and legality. The interim measures operate within the present society and serve as precursors to the preferred remedies. The experiences of the women and the limited use of the law both 'formed the basis for these recommendations. It is this researcher's submission that battering cannot be addressed adequately in legal terms alone. Seen as a means of social control of women, battering has to be dealt with at both the social and legal levels for any effective measures to be taken.